A comparative study of knowledge sharing pattern among the undergraduate and postgraduate students of private universities in Bangladesh. Issue 8 (28th October 2014) - Sabbir Rahman, Muhammad; Highe Khan, Abdul; Mahabub Alam, Md.; Mustamil, Norizah; Wei Chong, Chin
Abstract : Purpose: – The aim of this inquiry is to uncover the pattern of knowledge-sharing behaviour among the undergraduate and postgraduate students of private universities in Bangladesh. Design/methodology/approach: – This inquiry studied the knowledge-sharing pattern of undergraduate and graduate students by utilising a questionnaire-based open-ended survey from several private universities in Dhaka, Bangladesh. Apart from the descriptive statistics, the research used t -test to further explain the data. Findings: – This research focussed on seven areas of knowledge-sharing pattern. The data collected from 350 respondents from different private universities suggest that there are significant differences in the knowledge-sharing pattern between undergraduate and graduate students. Overall, this research documents that the postgraduate students have shown higher perceived attitudes towards knowledge sharing, compared to undergraduate students. Research limitations/implications: – This research applied a descriptive study to understand knowledge-sharing patterns among undergraduate and postgraduate students, rather than a correlational study to ascertain the relationship among variables. Practical implications: – This research has contributed to the knowledge-sharing research in several aspects. In fact, this study extended the research findings of Wei et al. (2012) by examining the patterns of knowledge sharing in a different socioeconomic environment. Although this research investigated the practice of knowledge sharing of undergraduate and postgraduate students by adapting the instrument of Wei et al. (2012), one of the significant contributions of this research is to explore the behavioural aspects of knowledge-sharing pattern among undergraduate and postgraduate students from different private universities in Bangladesh. By interpreting the knowledge-sharing pattern of undergraduate and postgraduate students of private universities, this inquiry will assist the government's policymakers, management of individual universities and academicians to come up with novel methods of instruction and to transform the knowledge-driven higher learning establishment. Originality/value: – The majority of studies on knowledge sharing have been conducted in an organisational context. This inquiry is one of few investigations to compare the knowledge-sharing patterns among undergraduate and postgraduate students in Bangladesh.